Blood Lipids and Cognitive Performance of Aging Polish Adults: A Case-Control Study Based on the PolSenior Project - McFarlane, Oliwia; Kozakiewicz, Mariusz; Kędziora-Kornatowska, Kornelia; Gębka, Dominika; Szybalska, Aleksandra; Szwed, Małgorzata; Klich-Rączka, Alicja (Frontiers in Aging Neuroscience, 2020)
Background: The demand for effective strategies of maintaining cognitive capableness and establishing early dementia diagnosis has been tremendous, especially in the context of population aging. However, studies on elderly population and neurocognitive impairment had provided ambiguous results throughout, while potential blood biomarkers of cognitive decline are yet to be clearly understood. Objectives: The present study is aimed at assessing the relationship between blood lipids - especially in the context of their usefulness as biomarkers of an early cognitive decline - and cognitive functioning of the aging adults. Material and methods: The study sample consisted of 230 participants,- (109 women, 121 men) aged 65+ years. Plasma 24(S)-hydroxycholesterol, serum total cholesterol (TC), high-density lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol (LDL) were assessed. The analyses were conducted in 3 groups of cognitive performance: cognitively normal, MCI, and mild dementia, of which the subjects were divided with the Mini-Mental State Examination (MMSE). Results: No significant differences in 24(S)-OHC plasma concentrations for different levels of cognitive performance were found. Significant differences were found in serum TC (p=0,026) and LDL (p=0,007) concentrations for different levels of cognitive performance. Concentrations of both parameters were highest in the MCI group and lowest in mild dementia and cognitive norm, respectively. No significant differences between serum HDL concentrations and cognitive performance were found. Conclusions: In order to fully assess the potential of research on blood lipids in regards with a cognitive decline, cross sectional or epidemiological studies aimed at further exploring blood lipid roles in both the early and advanced MCI and dementia, are needed.